Perkembangan Mikrobia Rumen dengan Pellet Complete Calf Starter pada Pedet Friesian Holstein - Nadia Maharani; Rinawidiastuti Rinawidiastuti (Universitas Muhammadiyah Purworejo, 2016)
This study aims to assess the quality of the Complete Calf Starter (CCS) formula with 5% molasses as a milk substitute for the development of pre-weaning Friesian Holstein calf rumen microbes. The materials used were 20 FH calves consisting of 14 females and 6 pre-weaning males aged 2 weeks with an average body weight of 45 ± 5 kg, feed ingredients consisting of milled corn, fine bran, soybean meal, straw. corn, molasses and minerals. The research was designed in a non-parametric descriptive manner. The variables observed were total battery and pH. The results showed that the total population of rumen fluid bacteria in calves aged 2 weeks was 80x106 Kol / ml, 4 weeks old was 40x106; 50x106 cabbage/ml and 6 weeks of age 20x106; 18x106 cabbage/ml. Rumen pH of calves 2 weeks old 5.71, 4 weeks old 5.54; 5,18 and 6 weeks of age 5,62; 5.48. Based on the results obtained, it can be concluded that the CCS pelleted form is able to stimulate the development of FH calf rumen at 2 weeks of age but at 4 and 6 weeks the total number of bacteria decreases.Keywords: Complete Calf Starter, Total Bacteria, pH